Aluminum alloy material and micro-arc oxidation treatment process thereof

By introducing air pressure parameters during microarc oxidation, the oxide film layer structure on the surface of aluminum alloy is optimized, and the corrosion resistance and wear resistance of aluminum alloy are solved, which is significantly improved and the service life is extended. .

CN119177481APending Publication Date: 2024-12-24姚雷
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411586146.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Aluminum alloys are prone to electrochemical corrosion in acidic corrosion environments, resulting in the damage of the passivation layer on the surface and cannot be effectively protected, which aggravates the corrosion and limits its application range.

Method used

By introducing air pressure parameters during microarc oxidation, the porosity and microscopic defects of the oxide film layer are controlled, the growth of the dense layer is optimized, and a microarc oxide film layer with high corrosion resistance is formed.

Benefits of technology

It significantly improves the corrosion resistance and wear resistance of aluminum alloys, and extends its service life, especially its reliability and service life in acidic environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

According to the aluminum alloy material and the micro-arc oxidation treatment process thereof, air pressure parameters are introduced in the micro-arc oxidation process, the corrosion resistance of a micro-arc oxidation film layer can be effectively improved, the corrosion resistance can be improved mainly by reducing the porosity, reducing microdefects and the like, the obtained micro-arc oxidation layer is thick, and the micro-arc oxidation treatment process is simple. And the roughness is low, and the corrosion resistance is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aluminum alloy surface treatment technology, and in particular to a treatment process for treating aluminum alloy materials by micro-arc oxidation. Background Art

[0002] Aluminum has strong chemical activity and is easily oxidized into aluminum oxide with poor stability and loose and porous surface in natural environment. At the same time, aluminum alloy and oxide film are prone to corrosion in acidic corrosive medium. The Cl in these acidic corrosive environments - Ions and acid radicals react with aluminum alloys, which in turn cause electrochemical corrosion, resulting in the destruction of the passivation layer on the surface of the aluminum alloy, which can no longer provide protection, causing the aluminum alloy to corrode. The acidic environment will cause the passivation layer on the surface of the aluminum alloy to be consumed, and the reaction between the aluminum alloy and the acid will produce hydrogen, which will intensify the corrosion. As a result, the application of aluminum alloys is restricted to a certain extent.

[0003] There are mainly the following types of corrosion of aluminum alloys: 1. Pitting corrosion, also known as pitting corrosion, usually occurs in local areas of the metal surface. It is a local corrosion phenomenon that manifests as small pits or holes. Pitting corrosion is usually caused by the metal surface being affected by corrosive media in a specific environment, such as a humid atmosphere, salt water, acidic or alkaline environment, resulting in a faster corrosion rate in the local area than in other areas. Pitting corrosion can cause damage and corrosion to the metal surface, thereby reducing its corrosion resistance and mechanical properties. The mechanism of pitting corrosion is mainly due to the fact that the metal surface is affected by the corrosive medium, forming a local electrochemical reaction system on the surface. In this reaction system, the anodic reaction rate in the local area is faster than the cathodic reaction rate, resulting in a greater release rate of metal ions in the area than in other areas, thereby causing local corrosion. Specifically, during the pitting process, microscopic pores or pits are formed in certain areas of the metal surface, and during the anodic reaction process in these areas, active ions on the metal surface are released, while electrons in the cathodic reaction process are absorbed. This will lead to an increase in the concentration of metal ions in the local area, forming an electrochemical reaction system in which the local area becomes the anode and other areas become the cathode, causing local corrosion. In addition, pitting is also affected by many factors, such as the chemical composition, crystal structure, surface state, properties of the corrosive medium, temperature, fluid velocity, etc. of the metal material. In practical applications, appropriate measures need to be taken according to the specific situation to reduce or avoid the occurrence of pitting. 2. Filiform corrosion. Filiform corrosion is a local corrosion phenomenon that usually occurs on the surface of filaments or tubular objects on the metal surface, manifested as linear or tubular corrosion pits along the metal surface. This corrosion mode is characterized by the formation of linear or tubular deep corrosion pits along the metal surface, rather than uniformly corroding the entire surface. Filiform corrosion usually occurs on the surface of metal materials such as stainless steel, copper, and aluminum, and the causes of its occurrence are relatively diverse, including defects on the metal surface, unevenness of the metal structure, composition and temperature of the corrosive medium, gas content and other factors. Filiform corrosion is a corrosion phenomenon that occurs on the surface of certain metals with special structures. In the process of filiform corrosion, some areas of the metal surface are prone to form electrochemical reaction systems due to the presence of filamentary or tubular defects or structures. These defects or structures become the starting points of filiform corrosion. Around these starting points, the anodic reaction rate in the local area is faster than the cathodic reaction rate, resulting in a greater release rate of metal ions in this area than in other areas, thus causing local corrosion.

[0004] 3. Stress corrosion. Stress corrosion is a corrosion phenomenon that occurs when metal materials are subjected to the dual effects of stress and specific corrosive media. Under the action of stress corrosion, the corrosion resistance of metal materials will be significantly reduced, resulting in cracks, embrittlement and other damage on the metal surface, and may even cause serious failure of parts. The mechanism of stress corrosion is relatively complex. It is generally believed that it involves multiple factors such as electrochemical reactions, physical and chemical changes of metals. Generally speaking, the occurrence of stress corrosion requires the following three conditions to be met at the same time: The presence of stress: When metal materials are under stress, their corrosion resistance will be reduced, making stress corrosion prone. The presence of corrosive media: Specific corrosive media have a strong corrosive effect on metal materials, causing corrosion on the metal surface. The presence of sensitivity: Factors such as the chemical composition, crystal structure, cold working or heat treatment of metal materials will affect their sensitivity, that is, their resistance to stress corrosion. 4. Galvanic corrosion. It usually occurs at the contact point between two different metals or alloys. When these metals or alloys are in an electrolyte or under the action of a corrosive medium, due to their potential difference, a battery will be formed and a current will be generated in the electrolyte. When one of the metals or alloys has a lower potential, it becomes the cathode of the electrochemical reaction, while the other metal or alloy with a higher potential becomes the anode of the electrochemical reaction. In this case, the metal ions on the surface of the anode metal or alloy are reduced by the anions in the electrolyte, while the metal ions on the surface of the cathode metal or alloy are reduced to metal.

[0005] At present, the widespread application of aluminum alloys is restricted by poor corrosion resistance. In order to solve this problem, many scholars are committed to studying the corrosion behavior and corrosion mechanism of aluminum alloys, seeking solutions from the root of the problem to provide direction for the protection and measures of aluminum alloys. At present, measures to enhance the corrosion resistance of aluminum alloys often use surface engineering technology to generate a protective film on the surface of aluminum alloys. This method not only helps to further expand the application range of aluminum alloys, but also improves the performance of the alloy to meet various specific application requirements. Through this method, the corrosion resistance of aluminum alloys has been effectively improved, so that it has been widely used in the industrial field. Therefore, this surface treatment technology provides important support and guarantee for the further development of aluminum alloys.

[0006] Compared with traditional anodizing technology, the advantage of microarc oxidation (MAO) is that when treating the metal surface, high-voltage arc discharge is used to form a microarc discharge reaction, so that the metal surface forms a dense, uniform, high-hardness and high-corrosion-resistant oxide film in the electrolyte, which is usually a ceramic film with matrix metal oxide as the main component. Microarc oxidation technology is suitable for a variety of metal materials, such as aluminum alloys, aluminum alloys, titanium alloys, etc., and can be treated in different types of electrolytes, such as alkaline, acidic, neutral, etc. Microarc oxidation technology can control the thickness, color and surface morphology of the oxide film by adjusting the processing parameters and electrolyte composition to meet different application requirements. Microarc oxidation technology has a wide range of applications. For example, it can be used to improve the surface hardness, corrosion resistance, wear resistance and other properties of metal materials in the fields of aviation, automobiles, ships, etc., and extend their service life. In the field of biomedicine, microarc oxidation technology can be used to prepare the surface of biomedical materials, improve their biocompatibility and bioactivity, and is expected to be used in the preparation of medical devices such as artificial bones and artificial joints. In conclusion, micro-arc oxidation technology is a surface treatment technology with broad application prospects, excellent performance and applicability, and is of great significance to material processing and application in many fields.

[0007] Micro-arc oxidation technology is different from traditional anodizing technology. This technology can enter the high-voltage discharge area and grow an oxide film in situ on the substrate surface through micro-arc discharge. Compared with other processes, the micro-arc oxidation film has a stronger bonding force with the substrate, good wear resistance and corrosion resistance, and is very effective in protecting the substrate. By adjusting the micro-arc oxidation process parameters, the growth process of the oxide film can be optimized. Therefore, in the research of aluminum alloy surface treatment, micro-arc oxidation technology has attracted much attention and can improve the comprehensive properties of aluminum alloys.

[0008] The film structure of micro-arc oxidation usually consists of two layers: a dense layer and a loose layer. The dense layer is a dense structure composed of oxides. It presents a uniform and dense structure on a microscopic scale and usually has high hardness and wear resistance. The dense layer is usually embedded and grown in situ with the substrate, forming an organic combination with the substrate metal, with almost no micropores and microcracks. This dense structure is conducive to improving the corrosion resistance of the film layer, and bears the heavy responsibility of blocking the corrosive medium. At the same time, it can also enhance the bonding force between the film layer and the substrate, but the thickness is very limited, only a few microns. The loose layer is a porous structure composed of many pores, usually located outside the dense layer. The pore size and distribution density of the loose layer are closely related to the parameters of the micro-arc oxidation process (such as voltage, current, electrolyte composition, etc.). The pore structure of the loose layer provides a certain adsorption capacity for the film layer, which can be used to adsorb substances such as lubricating oil, thereby improving the lubrication performance of the material. The corrosive medium will contact the substrate through the micropores and microcracks on the oxide film layer that enter the film layer, thereby increasing the contact area between the oxide film layer and the corrosive medium. This will cause the corrosive medium to penetrate into the oxide film faster, which will cause the corrosion resistance of the film to deteriorate, and even cause the oxide film to crack, fall off and corrode the base material. Therefore, when the traditional micro-arc oxidation film is exposed to neutral and acidic harsh environments for a long time, it cannot effectively block the corrosive medium and provide protection.

[0009] In practical applications, aluminum alloy workpieces may face acid rain erosion when exposed to the atmosphere, such as automobile bodies, aircraft parts, mobile phone cases, computer cases, water treatment equipment, sports equipment, medical equipment, etc. made of aluminum alloys, which are exposed to acidic media in many environments. These acidic media will corrode the surface of aluminum alloys. Therefore, it is very necessary to test the acid resistance of aluminum alloy micro-arc oxidation film. The acid resistance of aluminum alloy micro-arc oxidation film refers to the ability of the film to maintain good physical, chemical and mechanical properties for a long time in acidic medium. The purpose of testing acid resistance is to evaluate the service life and reliability of aluminum alloy micro-arc oxidation film in acidic environment, so as to reasonably design and apply this film. In addition, by testing the acid resistance of aluminum alloy micro-arc oxidation film, it can also provide a basis for formulating more scientific and reasonable anti-corrosion measures, which will help to further improve the application performance and service life of aluminum alloy. Summary of the invention

[0010] Based on the above-mentioned aluminum alloy being susceptible to corrosion and the improvement of corrosion resistance of micro-arc oxidation, the present invention provides an aluminum alloy material and a micro-arc oxidation treatment process thereof, and introduces gas pressure parameters during the micro-arc oxidation process. The corrosion resistance of the micro-arc oxidation film layer can be effectively improved by controlling the gas pressure parameters, and the corrosion resistance may be mainly improved by reducing the porosity and reducing microscopic defects.

[0011] Specifically: A micro-arc oxidation process for aluminum alloy comprises the following steps: (1) Surface treatment of aluminum alloy; (2) Implementing micro-arc oxidation; (3) Post-processing; The electrolytic cell used for micro-arc oxidation is a completely sealed electrolytic cell, a gas pressure control valve is arranged on the electrolytic cell cover, the surface treated aluminum alloy is placed in the electrolytic cell body containing electrolyte and serves as an anode, a stainless steel cathode is arranged on the electrolytic cell wall, the electrolytic cell is sealed, and the pressure of the electrolytic cell is controlled by a gas pressure control valve. After stabilization, the power supply is turned on to implement micro-arc oxidation. The power supply is a bipolar pulse power supply, the power supply adopts a constant current mode, the constant current density is 0.2-0.3A / dm2, the duty cycle is 30%-40%, the frequency is 400-600Hz, and the micro-arc oxidation treatment time is 5-30min.

[0012] Furthermore, the pressure index of the air pressure control valve is 6-12Mpa, and the gas in the air pressure control valve is air.

[0013] Furthermore, the micro-arc oxidation solution is composed of 2.0-2.3 g / L sodium hydroxide, 2.4-2.7 g / L sodium silicate and deionized water.

[0014] Furthermore, a stirrer is provided in the electrolytic tank, and the stirring speed is 100-200 rpm.

[0015] Furthermore, circulating cooling water is used to control the temperature of the electrolytic cell to 15-30°C.

[0016] Furthermore, the surface treatment of the aluminum alloy includes polishing, cleaning and drying, wherein the polishing is performed using silicon carbide sandpaper to polish to a mirror surface, and the drying is performed using cold air.

[0017] Furthermore, the aluminum alloy contains no more than 5 wt.% of magnesium metal.

[0018] Furthermore, the post-treatment includes washing with deionized water and drying, and sealing treatment can be performed after drying as needed.

[0019] It is known to those skilled in the art that micro-arc oxidation treatment can significantly improve the corrosion resistance and wear resistance of aluminum alloys, but defects such as the porosity and microcracks of the film make it no longer suitable for use in high-demand environments. The micro-arc oxidation process can be optimized by increasing the content of corrosion-resistant phase, reducing porosity, and reducing micro defects. The factors affecting micro-arc oxidation include electrical parameters, oxidation time, electrolyte, additives, pretreatment and post-treatment. Adjusting these parameters and optimizing the microstructure can improve the corrosion resistance of the film. This is one of the most commonly used optimization methods. For example, the higher the voltage, the greater the energy that promotes the growth of the film, the larger the size of the discharge spark, and the looser the film, thereby reducing the corrosion resistance of the oxide film. The increase in duty cycle may lead to an increase in discharge melt and the formation of large-diameter micropores, which is not conducive to the formation of a dense film.

[0020] In general, different electrical parameters will affect the thickness, surface structure and corrosion resistance of the film. It should be noted that electrical parameters will directly affect the energy of plasma discharge, and then affect the growth rate and density of the film, all of which will affect the corrosion resistance of the film.

[0021] However, there are few studies on the effect of gas pressure on the micro-arc oxidation film during the micro-arc oxidation process. The present invention obtains a highly corrosion-resistant micro-arc oxidation layer by controlling the pressure during the micro-arc oxidation process.

[0022] Beneficial technical effects: By introducing the gas pressure parameter in the micro-arc oxidation process, the corrosion resistance of the micro-arc oxidation film can be effectively improved, which may be mainly improved by reducing the porosity and reducing micro defects. In addition, the thickness of the obtained micro-arc oxidation layer varies in the range of 40-70μm, and the roughness is 1.3-1.6μm. Specifically, the thickness of Example 2 is about 45±2μm, and the roughness is 1.35±0.4μm; the micro-arc oxidation layer mainly exists in the form of aluminum-based oxide or silicon-based oxide, and the introduction of gas pressure does not have a significant effect on the coating composition. The gas pressure mainly affects the morphology and thickness of the pore structure, thereby improving the corrosion resistance of the micro-arc oxidation layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Attached Figure 1 Voltage-time response diagram under different conditions of Examples 1-4.

[0024] Attached Figure 2 The evolution of micro-discharge over time under the conditions of different Examples 1-4.

[0025] Attached Figure 3 Micro-arc morphology images and energy spectrum graphs under different conditions of Examples 1-4.

[0026] Attached Figure 4 Cross-sectional views of micro-arc oxidation of Example 2 and Blank Example.

[0027] Attached Figure 5 Corrosion effect diagram of the embodiment and the blank example. DETAILED DESCRIPTION Example 1

[0028] A micro-arc oxidation process for aluminum alloy comprises the following steps: (1) Surface treatment of aluminum alloy: grinding, cleaning and drying. The grinding is to use silicon carbide sandpaper to grind to a mirror surface. The drying is to use cold air to dry.

[0029] (2) Implementing micro-arc oxidation: The electrolytic cell used for implementing micro-arc oxidation is a completely sealed electrolytic cell, and a gas pressure control valve is provided on the electrolytic cell cover. The surface-treated aluminum alloy is placed in an electrolytic cell body containing an electrolyte and serves as an anode. A stainless steel cathode is provided on the wall of the electrolytic cell. The electrolytic cell is sealed, and a gas pressure control valve is used to control the pressure index of the electrolytic cell to 6 MPa. The gas in the gas pressure control valve is air. After stabilization, the power is turned on to implement micro-arc oxidation.

[0030] The power supply adopts a constant current mode, with a constant current density of 0.25A / dm2, a duty cycle of 35%, a frequency of 500Hz, and a micro-arc oxidation treatment time of 10min.

[0031] The micro-arc oxidation solution consists of 2.2 g / L sodium hydroxide, 2.5 g / L sodium silicate and deionized water.

[0032] The electrolytic tank is provided with a stirrer with a stirring speed of 150 rpm.

[0033] The temperature of the electrolytic cell was controlled at 22°C using circulating cooling water.

[0034] (3) Post-processing: including deionized water cleaning and drying. Example 2

[0035] A micro-arc oxidation process for aluminum alloy comprises the following steps: (1) Surface treatment of aluminum alloy: grinding, cleaning and drying. The grinding is to use silicon carbide sandpaper to grind to a mirror surface. The drying is to use cold air to dry.

[0036] (2) Implementing micro-arc oxidation: The electrolytic cell used for implementing micro-arc oxidation is a completely sealed electrolytic cell, and a gas pressure control valve is provided on the electrolytic cell cover. The surface-treated aluminum alloy is placed in the electrolytic cell body containing the electrolyte and serves as the anode. A stainless steel cathode is provided on the wall of the electrolytic cell. The electrolytic cell is sealed, and a gas pressure control valve is used to control the pressure index of the electrolytic cell to 8 MPa. The gas in the gas pressure control valve is air. After stabilization, the power is turned on to implement micro-arc oxidation.

[0037] The power supply adopts a constant current mode, with a constant current density of 0.25A / dm2, a duty cycle of 35%, a frequency of 500Hz, and a micro-arc oxidation treatment time of 10min.

[0038] The micro-arc oxidation solution consists of 2.2 g / L sodium hydroxide, 2.5 g / L sodium silicate and deionized water.

[0039] The electrolytic tank is provided with a stirrer with a stirring speed of 150 rpm.

[0040] The temperature of the electrolytic cell was controlled at 22°C using circulating cooling water.

[0041] (3) Post-processing: including deionized water cleaning and drying. Example 3

[0042] A micro-arc oxidation process for aluminum alloy comprises the following steps: (1) Surface treatment of aluminum alloy: grinding, cleaning and drying. The grinding is to use silicon carbide sandpaper to grind to a mirror surface. The drying is to use cold air to dry.

[0043] (2) Implementing micro-arc oxidation: The electrolytic cell used for implementing micro-arc oxidation is a completely sealed electrolytic cell, and a gas pressure control valve is provided on the electrolytic cell cover. The surface-treated aluminum alloy is placed in the electrolytic cell body containing the electrolyte and serves as the anode. A stainless steel cathode is provided on the wall of the electrolytic cell. The electrolytic cell is sealed, and a gas pressure control valve is used to control the pressure index of the electrolytic cell to 10 MPa. The gas in the gas pressure control valve is air. After stabilization, the power is turned on to implement micro-arc oxidation.

[0044] The power supply adopts a constant current mode, with a constant current density of 0.25A / dm2, a duty cycle of 35%, a frequency of 500Hz, and a micro-arc oxidation treatment time of 10min.

[0045] The micro-arc oxidation solution consists of 2.2 g / L sodium hydroxide, 2.5 g / L sodium silicate and deionized water.

[0046] The electrolytic tank is provided with a stirrer with a stirring speed of 150 rpm.

[0047] The temperature of the electrolytic cell was controlled at 22°C using circulating cooling water.

[0048] (3) Post-processing: including deionized water cleaning and drying. Example 4

[0049] A micro-arc oxidation process for aluminum alloy comprises the following steps: (1) Surface treatment of aluminum alloy: grinding, cleaning and drying. The grinding is to use silicon carbide sandpaper to grind to a mirror surface. The drying is to use cold air to dry.

[0050] (2) Implementing micro-arc oxidation: The electrolytic cell used for implementing micro-arc oxidation is a completely sealed electrolytic cell, and a gas pressure control valve is provided on the electrolytic cell cover. The surface-treated aluminum alloy is placed in the electrolytic cell body containing electrolyte and serves as an anode. A stainless steel cathode is provided on the wall of the electrolytic cell. The electrolytic cell is sealed, and a gas pressure control valve is used to control the pressure index of the electrolytic cell to 12 MPa. The gas in the gas pressure control valve is air. After stabilization, the power is turned on to implement micro-arc oxidation.

[0051] The power supply adopts a constant current mode, with a constant current density of 0.25A / dm2, a duty cycle of 35%, a frequency of 500Hz, and a micro-arc oxidation treatment time of 10min.

[0052] The micro-arc oxidation solution consists of 2.2 g / L sodium hydroxide, 2.5 g / L sodium silicate and deionized water.

[0053] The electrolytic tank is provided with a stirrer with a stirring speed of 150 rpm.

[0054] The temperature of the electrolytic cell was controlled at 22°C using circulating cooling water.

[0055] (3) Post-processing: including deionized water cleaning and drying.

[0056] Blank Example: A micro-arc oxidation process for aluminum alloy, comprising the following steps: (1) Surface treatment of aluminum alloy: grinding, cleaning and drying. The grinding is to use silicon carbide sandpaper to grind to a mirror surface. The drying is to use cold air to dry.

[0057] (2) Implementing micro-arc oxidation: The surface-treated aluminum alloy is placed in an electrolytic cell containing an electrolyte and used as an anode. A stainless steel cathode is provided on the wall of the electrolytic cell. The cell is open and the power is turned on to implement micro-arc oxidation.

[0058] The power supply adopts a constant current mode, with a constant current density of 0.25A / dm2, a duty cycle of 35%, a frequency of 500Hz, and a micro-arc oxidation treatment time of 10min.

[0059] The micro-arc oxidation solution consists of 2.2 g / L sodium hydroxide, 2.5 g / L sodium silicate and deionized water.

[0060] The electrolytic tank is provided with a stirrer with a stirring speed of 150 rpm.

[0061] The temperature of the electrolytic cell was controlled at 22°C using circulating cooling water.

[0062] (3) Post-processing: including deionized water cleaning and drying.

[0063] Figure 1 Respectively represent the voltage-time response and the attachment under different conditions of Examples 1-4. Figure 2 The corresponding micro-discharges evolve over time. The typical voltage-time response during the micro-arc oxidation process of the micro-arc oxidation layer constitutes a rapidly growing coating and is the main factor affecting the breakdown voltage, rather than the difference in gas pressure. However, under different gas pressure conditions, the voltage-time behavior after the breakdown voltage is different. For example, the applied frequency (critical voltage) in Example 2 delays the increase in voltage. On the other hand, in the absence of a critical voltage in Examples 1, 3, and 4, the voltage continues to increase gradually throughout the PEO coating process, which means that the micro-discharge develops into a local arc discharge. In the final stage, Example 4 produced a maximum voltage of 660V, while Example 2 produced a minimum voltage of 594V. Generally, micro-arc oxidation includes the following stages, as shown in the attached Figure 2 As shown: (1) Breakdown voltage stage: uniform distribution of microdischarges on the surface (color: white); (2) Intermediate stage: microdischarge density decreases but size increases (color: yellow); (3) Final stage: microdischarge density further decreases and transforms into arcs (color: orange). Compared with the examples, Example 2 has a relatively high microdischarge intensity, which is particularly evident at the breakdown voltage.

[0064] See attached Figure 3 The morphology of the micro-arc oxidation layer and the corresponding energy spectrum analysis show that the implementation of gas pressure assistance during the micro-arc oxidation process will cause the micro-arc oxidation surface to present a pore structure with relatively small pores. The pore structure is generated when the molten substrate material is ejected from the coating-substrate interface by high-temperature plasma and is rapidly solidified by the electrolyte at a relatively low temperature. The existence of the central hole indicates the discharge channel for the ejection of the aluminum matrix melt, wherein Example 2 is compared with other embodiments, and the attached Figure 4 For the blank example in the figure, a relatively dense oxide layer is shown, including the density of the internal and surface coatings. The elemental composition of the surface of the micro-arc oxidation coating contains aluminum, magnesium, silicon, oxygen and a trace amount of potassium, among which aluminum and magnesium are derived from the matrix, while potassium and silicon are electrolyte components, that is, the micro-arc oxidation layer mainly exists in the form of aluminum-based oxide or silicon-based oxide. The introduction of gas pressure does not have a significant effect on the coating composition. The gas pressure mainly affects the morphology and thickness of the pore structure and improves the corrosion resistance of the micro-arc oxidation layer. For details, please refer to the attached Figure 5 .

[0065] In addition, under different air pressure conditions, especially compared with the blank example, the thickness and surface roughness of Example 2 vary significantly. For example, the thickness of Examples 1-4 varies in the range of 40-70 μm, and the roughness is 1.3-1.6 μm. Specifically, the thickness of Example 2 is about 45±2 μm, and the roughness is 1.35±0.4 μm. In comparison, the thickness of the blank example varies in the range of about 30±7 μm, and the roughness is 4.7±1.5 μm.

[0066] See attached Figure 5 The corrosion potential test curve of the blank case is 3.2*10 -7 A / cm 2 , the corrosion voltage is -0.812V. In comparison, the optimal corrosion current density of Example 2 is 2.9*10 -8 A / cm 2 , the corrosion voltage is -0.671V, showing better corrosion resistance, which matches its morphology and cross-sectional images.

[0067] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A micro-arc oxidation process for aluminum alloy, characterized in that The steps include: (1) Surface treatment of aluminum alloy; (2) Implementing micro-arc oxidation; (3) Post-processing; The electrolytic cell used for micro-arc oxidation is a completely sealed electrolytic cell, a gas pressure control valve is arranged on the electrolytic cell cover, the surface treated aluminum alloy is placed in the electrolytic cell body containing electrolyte and serves as an anode, a stainless steel cathode is arranged on the electrolytic cell wall, the electrolytic cell is sealed, and the pressure of the electrolytic cell is controlled by a gas pressure control valve. After stabilization, the power supply is turned on to implement micro-arc oxidation. The power supply adopts a constant current mode, with a constant current density of 0.2-0.3A / dm2, a duty cycle of 30%-40%, a frequency of 400-600Hz, and a micro-arc oxidation treatment time of 5-30min.

2. A micro-arc oxidation process for aluminum alloy according to claim 1, characterized in that The pressure index of the air pressure control valve is 6-12Mpa, and the gas in the air pressure control valve is air.

3. A micro-arc oxidation process for aluminum alloy according to claim 1, characterized in that The micro-arc oxidation solution is composed of 2.0-2.3 g / L sodium hydroxide, 2.4-2.7 g / L sodium silicate and deionized water.

4. A micro-arc oxidation process for aluminum alloy according to claim 1, characterized in that The electrolytic tank is provided with a stirrer, and the stirring speed is 100-200 rpm.

5. The micro-arc oxidation process for aluminum alloy according to claim 1, characterized in that The temperature of the electrolytic cell is controlled at 15-30°C using circulating cooling water.

6. A micro-arc oxidation process for aluminum alloy according to claim 1, characterized in that The surface treatment of the aluminum alloy includes grinding, cleaning and drying. The grinding is to use silicon carbide sandpaper to grind to a mirror surface, and the drying is to dry with cold air.

7. A micro-arc oxidation process for aluminum alloy according to claim 1, characterized in that The aluminum alloy contains no more than 5 wt.% of magnesium metal.

8. The micro-arc oxidation process for aluminum alloy according to claim 1, characterized in that The post-treatment includes cleaning with deionized water and drying, and sealing treatment can be performed after drying as needed.

9. An aluminum alloy material, characterized in that An aluminum alloy material obtained by the treatment process as described in any one of claims 1-8.